Managing Conflict among Employees during Remote Work - Nurzyński, Filip (Zarządzanie konfliktami pomiędzy pracownikami w warunkach pracy zdalnej, 2023)
The article aims to recognise and investigate how remote work affects employees, the relations between them, and the methods of conflict resolution that are most often used by virtual teams. The conducted research made it possible to gather information and formulate conclusions. Summarizing the study results, one can state that employees appreciate remote work, however they struggle with problems resulting from the lack of a social aspect that is visible during digital work. Weaker communication efficiency and a deterioration of employee relations can lead to conflict situations. A solution that can deal with this problem may be the introduction of team-building activities by organizations which, given the survey results, are not provided by most companies. As a result, better relations can be established between employees, but also the effectiveness of communication should increase.
s. 119-131
Keywords: conflict; managing conflicts; virtual teams; remote work; konflikty; zarządzanie konfliktami; zespoły wirtualne; praca zdalna